1973
DOI: 10.1079/bjn19730094
|View full text |Cite
|
Sign up to set email alerts
|

Relation between diet and protozoal population in the rumen

Abstract: I . Four feeding trials were made to investigate relations between diet and protozoal population in the rumen.2. When a ration containing no concentrate was used, the number of entodiniomorphs decreased rapidly. The number of entodinioniorphs increased with the amount of concentrate.Rice straw, which was used as a sole source of roughage, was not always necessary for protozoa to survive in the rumen.3. The type of diet affected the holotrich population to a much smaller extent than the entodiniomorph populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 4 publications
3
20
0
Order By: Relevance
“…This is consistent with results of a preceding study obtained with rumen fluid from cows fed grass or hay as basic components and increasing amounts of concentrate (Müller et al, 1998). It is well known that the total number of protozoa increases when the level of concentrate in the total diet is increased up to a threshold level of about 60% (related to DM), this level being accompanied by less than 10% of structural fibre Abe et al, 1973;Lyle et al, 1981;Jouany, 1988). According to Dehority and Orpin (1988), diets containing 40 to 50% roughage will support maximum protozoal numbers with a diverse fauna.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with results of a preceding study obtained with rumen fluid from cows fed grass or hay as basic components and increasing amounts of concentrate (Müller et al, 1998). It is well known that the total number of protozoa increases when the level of concentrate in the total diet is increased up to a threshold level of about 60% (related to DM), this level being accompanied by less than 10% of structural fibre Abe et al, 1973;Lyle et al, 1981;Jouany, 1988). According to Dehority and Orpin (1988), diets containing 40 to 50% roughage will support maximum protozoal numbers with a diverse fauna.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, %grass did not influence Isotrichidae. Isotrichidae may be less affected by changes in the diet than other protozoa groups (Abe et al , 1973). Notably, Isotrichidae were observed in relevant proportions not only in large grazing ruminants but also in the largest browsing ruminant, the giraffe Giraffa camelopardalis (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that lowering of rumen pH by feeding high concentrate diets markedly lowers protozoa concentrations (Latham et al,1971;Abe et al, 1973;Mackie et al,1978;Towne et al, 1988;Franzolin and Dehority, 1996). Dehority (2005), working in vitro with monocultures of Entodinium caudatum, Entodinium exiguum, Epidinium caudatum and Ophryoscolex purkynjei, observed that numbers of all four species decreased markedly below pH 5.8 and the protozoa were no longer viable at a pH of 5.3.…”
Section: Resultsmentioning
confidence: 99%